KNOWLEDGE OF NURSES ABOUT INVASIVE MECHANICAL VENTILATION: LITERATURE REVIEW - Vieira Pessoa Rolim, Edlane; Lívia Silva Fonseca Moreira de Medeiros, Renata; de Lira Silva, Macerlane; Silva Oliveira, Geane (Health and Society, 2023)
INTRODUCTION: Mechanical ventilation (MV), in recent years, has been considered the main alternative to replace, totally or partially, the respiratory function of patients in pathological conditions, especially in cases of acute respiratory failure (ARF). It consists, basically, in the use of a mechanical device that will artificially provide the body with the necessary ventilation and oxygenation to maintain life. Its main function is to send a volume of air (ventilate), with a determined concentration of oxygen (FiO2) per unit of time (minute) in order to perform gas exchange, and can be applied invasively or non-invasively with positive pressure in the airways. OBJECTIVE: Faced with the presented problem, the objective was, in the light of the scientific literature, to identify the knowledge of nurses about invasive mechanical ventilation. METHODOLOGY: This is an integrative literature review, whose bibliographic survey was carried out from December 2022 to January 2023, in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS); Medical Literature Analyzes and Retrieval System Online (MEDLINE), Spanish Bibliographic Index of Health Sciences (IBECS) and the Nursing Database (BDENF) indexed in the Virtual Health Library (VHL) portal. In the aforementioned databases, the advanced search method was applied, categorizing the titles and abstracts, where the search was performed by crossing the following Health Sciences Descriptors (DeCS): “Nurses and Nurses”; “Artificial respiration”; “Mechanical ventilation” using the Boolean AND operator. Taking into account the following inclusion criteria: complete articles, available for download and reading in full; published in Portuguese, English and Spanish, in the last 05 years and excluding duplicate articles in the databases. The data obtained were extracted in full, and a descriptive-interpretive synthesis was elaborated, discussed in the light of the scientific literature pertinent to the study theme. RESULTS AND DISCUSSION: the results point to a limited knowledge of nursing professionals about invasive mechanical ventilation. Care practices such as: pain management, sedation control, mobilization, attention to clinical parameters, pressure injury prevention and applicability of Care Systematization are essential to direct quality care. Thus, the need for training emerges from the permanent education process. CONCLUSION: Through the results presented, it can be considered that the objective of this research was achieved, allowing to demonstrate the knowledge of the nursing professional regarding the patient under invasive mechanical ventilation. In view of this, it is evident that the deficiencies and lack of professional skills exist, however, there are strategies that can be devised to reverse this reality.